Financing Firms in India - Allen, Franklin; Chakrabarti, Rajesh; De, Sankar; Qian, Jun; Qian, Meijun (World Bank, Washington, DC, 2012)
The authors examine the legal and business environments, financing channels, and governance mechanisms of various types of firms in India and compare them to those from other countries. Despite its English commonlaw origin, strong legal protection provided by the law, and a democratic government, corruption within India's legal system and government significantly weakens investor protection in practice. External financing of firms has been dominated by nonmarket sources of financing, while the characteristics of listed firms are similar to those from countries with weak investor protection. The evidence, including results based on a survey of small and medium-scale private firms, shows that alternative financing channels provide the most important source of funds. The authors also find that informal governance mechanisms, such as those based on reputation, trust, and relationships are more important than formal mechanisms (such as courts) in resolving disputes, overcoming corruption, and supporting growth.